Temperature Control of Quartz-Glass Melting Areas in Laser Additive Manufacturing - Jing Chen; Zeping Lv; Xuanjia Zhang; Tao Xu; Yuntao Cheng (Micromachines)
Direct energy deposition is an additive technology that can quickly manufacture irregularly shaped quartz-glass devices. Based on this technology and coaxial laser/wire feeding, open-loop tests were conducted under different process parameters. A closed-loop temperature control system was designed and built for the molten pool temperature in quartz-glass additive manufacturing. It was based on a PID (proportional–integral–derivative) control algorithm for adjusting laser power. Changes in the macroscopic morphology, microstructure, and other qualities of the final additive result before and after the temperature control of the quartz glass were examined. Relative to constant laser powers of 120 W and 140 W, the temperature control of the multi-pass single-layer lateral additives produced dense surface microstructures of the additively produced quartz glass, and the molding quality was better.